Grandes projetos urbanos como reprodução da lógica do capital em Maringá (PR) - Töws, Ricardo Luiz (2015)
Urban planning has been justification to urban marketing, urban entrepreneurship or transformation of urban governance, public-private partnership, with a new look termed as strategic planning cities, coming from the neoliberal model that affects the cities, facing the economic globalization process which at its core is the spectacle of the city production. In the analysis on urban planning Maringa (PR), have come by its various stages and we try to understand or grasp that the large urban projects that are designed and implemented in the city are linked to the model that has already achieved several cities in the world, or by attraction mega events, sometimes as justification for 'requalify', 'urbanize' or boost urban development through major interventions and large urban projects. For this understanding, we set the goal of analyzing the urban planning and the production of urban space in Maringa (PR), to understand the logic of State and the agents in the production of urban laws, the Great Urban Projects and consequently the production of city to expanded reproduction of capital. To understand the urban geography, we analyze the formation of socio-spatial, urban sprawl and the process of vertical integration, especially guided by the analysis of the regulation to define the duration of the regulatory urban planning. Accordance with the approach of scale, Maringa has some features that allow the understanding of the agenda on cities, where urban policy is fragile, to allow the hegemonic groups able to play their strategies and actions, enabling the city to the expanded reproduction the capital, so the land values and property, and, on the opposite, preventing the city to the population. Are used modern representation of technologies that produce social alienation, putting the city in evidence and enhancing the urban land, to justify the city and puts it up for sale for big business. In fact, the practices are traditional, disguised as great things, whose argument comes from our recent past, traditional societies and archaic social relations, breeding in urban scale to ensure the hegemony of the elites on the process of production of the city. The Great Urban Projects analyzed are the New Center (Agora Project), Zone 10, the Eurogarden Design and the Industrial City of Maringá.